Chronic Voluntary Alcohol Drinking Causes Anxiety-like Behavior, Thiamine Deficiency, and Brain Damage of Female Crossed High Alcohol Preferring Mice - Xu, Hong; Li, Hui; Liu, Dexiang; Wen, Wen; Xu, Mei; Frank, Jacqueline A.; Chen, Jing; Zhu, Haining; Grahame, Nicholas J.; Luo, Jia (Frontiers in Pharmacology, 2021)
The central nervous system (CNS) is vulnerable to chronic alcohol abuse, and alcohol dependence is a chronically relapsing disorder which causes a variety of physical and mental disorders. Appropriate animal models are important for investigating the underlying cellular and molecular mechanisms. The crossed High Alcohol Preferring (cHAP) mice prefer alcohol to water when given free access. In the present study, we used female cHAP mice as a model of chronic voluntary drinking to evaluate the effects of alcohol on neurobehavioral and neuropathological changes. The female cHAP mice had free-choice access to 10% ethanol and water, while control mice had access to water alone at the age of 60-day-old. The mice were exposed to alcohol for 7 months then subjected to neurobehavioral tests including open field (OF), elevated plus maze (EPM), and Morris water maze (MWM). Results from OF and EPM tests suggested that chronic voluntary drinking caused anxiety-like behaviors. After behavior tests, mice were sacrificed, and brain tissues were processed for biochemical analyses. Alcohol altered the levels of several neurotransmitters and neurotrophic factors in the brain including gamma-Aminobutyric acid (GABA), corticotropin-releasing factor (CRF), cAMP response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF). Alcohol increased the expression of neuroinflammation markers including interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and C-C chemokine receptor 2 (CCR2). Alcohol also induced cleaved caspase-3 and glial fibrillary acidic protein (GFAP), indicative of neurodegeneration and gliosis. In addition, alcohol inhibited the expression of thiamine transporters in the brain and reduced thiamine levels in the blood. Alcohol also caused oxidative stress and endoplasmic reticulum (ER) stress, and stimulated neurogenesis.